Pengembangan Kawasan Waduk Mulur Sebagai Kawasan Wisata Edukasi Dan Sport - Yusuf, Muhammad, Dr. Ir. Qomarun, MM, Wisnu Setiawan, ST., M.Arch., PhD (2016)
In striving regional development to increase society prosperity and also earnings of countryside and earnings of local government Waduk Mulur area is inclusive of regional sub of development III covering upstate Bendosari, south and east of is inclusive of Ductile Accumulating basin where potency majored by is agriculture plant the food, fishery, industrial, plantation, ranch, industrial minimize the, housing and tourism. Waduk Mulur having very interesting panorama with the its irrigating atmosphere cooling, green view. Waduk Mulur which is located in Countryside Mulur and Countryside Mertan, Subdistrict Bendosari represent the part of system of resource management irrigate as well as as area of environmental management and conservation. So much Waduk Mulur function besides as absorbtion poke irrigate, also as floods operation. The accumulating basin represent the accumulating basin of brand develop;builded by Dutch Government in the year 1926, and hereinafter in the year 1940 the accumulating basin widened by Sunan Pakubuwono VI, so that have the areal pond for the width of 141,26 hectare. Especial target from the accumulating basin, none other than to answer the demand the irrigation water in area Sukoharjo. At that moment condition irrigate abundance, and all surface of accumulating basin suffused by water. Nature of clear water without existence of crop which grow for as intruder plant. Condition in this time have very paying attention to where its facilitys start to destroy, a lot of wild building, and happened by the superficiality caused by the happening of mud precipitation. Incoming tourist become to decrease because condition of accumulating basin this time is true to be made by a tourism place. The before to make again Waduk Mulur area as tourism place needed by a development and correct the insuffiency owned by the Waduk Mulur. By making new attraction tourism that is athletic and educative tourism by exploiting experienced potency of Waduk Mulur like fish, irrigate and its continent is wide as object. Expected by a Waduk Mulur become the pre-eminent wisata and can open the employment for society of about. Others is also needed by cooperation of between government and society for the shake of the target creation and give the counselling guidance to society of so that continuity and beauty of Waduk Mulur remain to be awaked to the last a period.